Mechanical and microstructural characteristics of Ti6Al4V/AA2519 and Ti6Al4V/AA1050/AA2519 laminates manufactured by explosive welding. (5th December 2016) - Bazarnik, P.; Adamczyk-Cieślak, B.; Gałka, A.; Płonka, B.; Snieżek, L.; Cantoni, M.; Lewandowska, M.
Abstract: The aim of the work was to produce laminated structures consisting of Ti–6Al–4V alloy and AA2519 plates and to investigate their microstructure and mechanical properties with an emphasis on the role of an additional AA1050 interlayer. Explosive welding was selected as a joining technology. The microstructure and chemical composition of the explosively joined samples were investigated. Mechanical properties were evaluated in the tensile testing and by microhardness analysis. The results demonstrated that explosive welding is an effective way to produce Ti/Al laminates. Both Ti6Al4V/AA2519 and Ti6Al4V/AA1050/AA2519 laminated plates exhibit good quality of bonding without voids and major delamination. The explosive welding produced metallurgical bonding with a nanostructured zone consisting of Al3 Ti and Al2 Ti phases. This zone is thicker in the joint with additional AA1050 interlayer when compared to direct AA2519/Ti6Al4V bonding. In the latter, SEM and STEM analysis reviled the presence of net-like structure in the collision zone. Advanced EDX analysis shows the enrichment of grain boundaries in copper. The formation of this structure is widely discussed. In addition, the explosive welding introduces large plastic deformation which induces the process of grain refinement in aluminium plates. Tensile testing confirms that joining section is not the weakest element of the cladded plates. Graphical abstract: Highlights: The microstructure and strength of interface joints strongly depends on the presence of additional AA1050 plate Good quality of joints was confirmed in tensile testing, as the joints have never been the weakest element of the laminates Ti6Al4V/AA2519 and Ti6Al4V/AA1050/AA2519 laminate plates were successfully obtained through explosive welding; EXW introduces into both aluminium plates a highly localized plastic deformation, which causes significant grain refinement